Deliberating for sustainability: lessons from the Porto Alegre experiment with participatory budgeting. Issue 1 (2nd January 2019) - Calisto Friant, Martin
ABSTRACT: This paper analyses the practice of participatory budgeting in Porto Alegre, Brazil, through an interdisciplinary lens that combines the theories of right to the city, environmental justice and deliberative democracy. It examines the democratic and deliberative nature of the participatory process as well its social, environmental and ecological outcomes. While participatory budgeting has been widely studied and internationally recognised, it has rarely been assessed in its ability to bring about urban sustainability. This analysis demonstrates that it is principally the deliberative nature of the participatory process that has allowed it to have a positive impact on the urban environment. In doing so, this article proposes key recommendations to successfully replicate this mechanism in order to face the various environmental and social challenges of the Anthropocene and contribute towards achieving the sustainable development goals.